Mizoram Planning and Development Department Draft Fifth Five Year Plan 1974-79 Vol. I - Planning Commission (Planning Commission, 1974)
The Union Territory of Mizoram, lying- between 22.00° and 24.90° (II, Lati. buds ) ax..d 92.20° E and 93.30° E(Longitude) , is situated in the easternmost corner of India, fl ankari by Bangladesh, and Tripura State in the ""'Jest and Burma in the East. Ir me north it has a boundary with lianipur State and Cachar district of Assam State. Tnc- Union Territory was a Kill i'istricts of Assam ana was curvec. out as a Union Torritory witri effect from the 21st January, 1972.
Draft Fifth Five Year Plan 1974-79 Vol. I